Respuesta :

Answer:

M=-8

Step-by-step explanation:

21+6m=3(m−1)

Step 1: Simplify both sides of the equation.

21+6m=3(m−1)

21+6m=(3)(m)+(3)(−1)(Distribute)

21+6m=3m+−3

6m+21=3m−3

Step 2: Subtract 3m from both sides.

6m+21−3m=3m−3−3m

3m+21=−3

Step 3: Subtract 21 from both sides.

3m+21−21=−3−21

3m=−24

Step 4: Divide both sides by 3.

3m/3=-24/3

M=-8

Answer:

m = - 8

Step-by-step explanation:

Given

21 + 6m = 3(m - 1) ← distribute

21 + 6m = 3m - 3 ( subtract 3m from both sides )

21 + 3m = - 3 ( subtract 21 from both sides )

3m = - 24 ( divide both sides by 3 )

m = - 8